2012 5th International Workshop on Co-Operative and Human Aspects of Software Engineering (CHASE) 2012
DOI: 10.1109/chase.2012.6223029
|View full text |Cite
|
Sign up to set email alerts
|

What affects team behavior? Preliminary linguistic analysis of communications in the Jazz repository

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

7
0

Authors

Journals

citations
Cited by 11 publications
(38 citation statements)
references
References 43 publications
4
34
0
Order By: Relevance
“…Although these omissions may be interpreted as representing a confounding factor due to contextual ignorance, we in fact know that the context is software development; and what is of interest, and is being captured by the tool, is evidence of attitudes. Previous work has also provided confirmation for the utility of the LIWC dictionary for examining software developers' attitudes [11].…”
Section: Linguistic Analysis Techniquesmentioning
confidence: 92%
See 2 more Smart Citations
“…Although these omissions may be interpreted as representing a confounding factor due to contextual ignorance, we in fact know that the context is software development; and what is of interest, and is being captured by the tool, is evidence of attitudes. Previous work has also provided confirmation for the utility of the LIWC dictionary for examining software developers' attitudes [11].…”
Section: Linguistic Analysis Techniquesmentioning
confidence: 92%
“…These theories may also be applicable for software engineering teams [11]. The absence of specific team attitudes and knowledge sharing behaviors may throw out team balance and challenge project success.…”
Section: Background and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…We also used the LIWC tool in a preliminary study of three different project areas from the Jazz repository to reveal cues for the way different teams work. In that study we found variances in behaviors among those solving different forms of software tasks [31], which led us to conjecture that the project environment may have contributed to these differences in behaviors. While we systematically examined three different project areas, probing team behaviors over different phases of their projects, and looked closely at specific team members [31], this initial study was largely exploratory and we only examined a small sample of artifacts which limited our level of inferences.…”
Section: Linguistic Analysis Techniquesmentioning
confidence: 93%
“…During a large-scale project utilizing a multiple case study design to investigate team evolution and dynamics within the IBM Rational Jazz repository we observed that a few individuals dominated project interactions (see [31] where we examine the effect of project environment (project type, people involved) on team behaviors). These variations were detected while examining sociograms we created from practitioners' messages during initial SNA explorations (see Figure 1 for an illustration).…”
Section: Methods and Measuresmentioning
confidence: 99%